Academic performance and moral competence: A match made in heaven? - Umaru Mustapha Zubairu; Chetubo Kuta Dauda; Olalekan Busra Sakariyau; Isa Imam Paiko (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2016)
This study aims to empirically assess the relationship between accounting students' academic performances and moral competencies by focusing on final-year accounting students enrolled at the International Islamic University Malaysia (IIUM). The students' moral competencies were measured using a scenario-based instrument developed through a collaboration with Islamic accounting scholars, called the Muslim Accountant Moral Competency Test (MAMOC), whilst students' academic performances were measured using their Cumulative Grade Point Averages (CGPAs). Contrary to the expected positive relationship between these two variables, the study found a negative, and insignificant, relationship. The implication of this result is that IIUM's Accounting Department needs to conduct a comprehensive review of the ethical content of its courses and use a more effective strategy of how to more effectively integrate Islamic values into the curriculum. Additionally, institutionalizing a measure of students' moral competencies would enable the department to objectively determine how well it is doing in developing the moral competencies of its students.